Neighborhood disadvantage is associated with actigraphy-assessed sleep continuity and short sleep duration. Issue 10 (16th July 2018) - Troxel, Wendy M; DeSantis, Amy; Richardson, Andrea S; Beckman, Robin; Ghosh-Dastidar, Bonnie; Nugroho, Alvin; Hale, Lauren; Buysse, Daniel J; Buman, Matthew P; Dubowitz, Tamara
Abstract: Study Objectives: Neighborhood disadvantage has been linked to poor sleep. However, the extant research has primarily focused on self-reported assessments of sleep and neighborhood characteristics. The current study examines the association between objective and perceived neighborhood characteristics and actigraphy-assessed sleep duration, efficiency, and wakefulness after sleep onset (WASO) in an urban sample of African American adults. Methods: We examined data from predominantly African American adults ( n = 788, mean age 55 years; 77% female) living in two low-income neighborhoods. Perceived neighborhood characteristics included safety, social cohesion, and satisfaction with one's neighborhood as a place to live. Objective neighborhood conditions included walkability, disorder, street lighting, and crime levels. Sleep duration, efficiency, and WASO were measured via 7 days of wrist-worn actigraphy. Analyses estimated each of the sleep outcomes as a function of perceived and objective neighborhood characteristics. Individual-level sociodemographics, body mass index, and psychological distress were included as covariates. Results: Greater perceived safety was associated with higher sleep efficiency and shorter WASO. Higher levels of crime were associated with poorer sleep efficiency and longer WASO, but these associations were only evident in one of the neighborhoods. Several interactions emerged suggesting that the association between neighborhood characteristics and sleep outcomes differed by neighborhood. Conclusions: Both how residents perceive their neighborhood safety and their exposure to objectively measured crime have implications for sleep continuity. These findings suggest that neighborhood conditions may contribute to disparities in sleep health.